2014
DOI: 10.1038/srep05126
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness of Problem-Based Learning of Preventive Medicine Education in China

Abstract: Problem-based learning (PBL) is defined as a student-centered pedagogy which can provide learners more opportunities for application of knowledge acquired from basic science to the working situations than traditional lecture-based learning (LBL) method. In China, PBL is increasingly popular among preventive medicine educators, and multiple studies have investigated the effectiveness of PBL pedagogy in preventive medicine education. A pooled analysis based on 15 studies was performed to obtain an overall estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 15 publications
2
27
0
2
Order By: Relevance
“…According to a survey of 123 medical schools in the United States, 70% of the medical schools use PBL especially during the preclinical years. 19 PBL pedagogy has been successfully implemented in medicine, [20][21][22][23][24][25][26] …”
Section: -6mentioning
confidence: 99%
“…According to a survey of 123 medical schools in the United States, 70% of the medical schools use PBL especially during the preclinical years. 19 PBL pedagogy has been successfully implemented in medicine, [20][21][22][23][24][25][26] …”
Section: -6mentioning
confidence: 99%
“…Além disso, 98,18% dos participantes declararam que o método PBL proporciona competência para a resolução de problemas. Outro estudo de análise retrospectiva mostrou perspectivas semelhantes sobre este nó crítico, apontando a habilidade de resolver problemas como uma das características de grande destaque do estudante nesse método (DING et al, 2014). Tal dado é de suma importância, levando em consideração o cotidiano desses futuros médicos, o qual corriqueiramente irão se deparar com entraves que precisarão rapidamente serem resolvidos para se ter um fim almejado.…”
Section: Resultsunclassified
“…O método propõe a elaboração de situações de ensino que promovam uma aproximação crítica do aluno com a realidade; a reflexão sobre problemas que geram curiosidade e desafio; a disponibilização de recursos para pesquisar problemas e soluções; a identificação e organização das soluções hipotéticas mais adequadas à situação e à aplicação dessas soluções (SOBRAL; CAMPOS, 2012). Entre as maiores dificuldades que o aluno se depara nessa metodologia estão as fragilidades relacionadas com a dificuldade de análise de questões, capacidade de síntese, relacionada aos conteúdos estudados e capacidade de seleção e classificação das prioridades relacionadas aos conteúdos a serem estudados (DING, 2014).…”
Section: Introductionunclassified
“…It has been suggested that during the problem-solving process, medical students not only acquire new clinical knowledge, but also develop their problem-solving abilities (Jonassen, 2011;Neville, 2009). This hypothesis has been evidenced by many previous studies (Choi, Lindquist, & Song, 2014;Ding et al, 2014;Karantzas et al, 2013;Klegeris, Bahniwal, & Hurren, 2013;Klegeris & Hurren, 2011;Pedersen & Liu, 2002). For example, Ding et al (2014) performed a meta-analysis on 15 studies in preventive medicine in which the effectiveness of PBL on problem solving was examined using medical examinations and questionnaires, and concluded that compared to traditional lecture-based learning (LBL), PBL was more effective in improving the problem-solving abilities of medical students.…”
Section: Introductionmentioning
confidence: 86%